Паньтэм тёзка: нылпиослы кылбуръёс, поэма / Семен Карпов - Карпов Семен Карпович (Инвожо, 2008)
Экземпляры: (20161201) / Инвентарный номер: 49156 / Цена: 40.00 / Авт.знак: К 26 / ГРНТИ: 17.82.93 / ББК: 84(2Рос= Удм)